2005
DOI: 10.1016/j.ejvs.2005.02.035
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Angioplasty as the First-choice Revascularization Procedure in Diabetic Patients with Critical Limb Ischemia: Prospective Study of 993 Consecutive Patients Hospitalized and Followed Between 1999 and 2003

Abstract: PTA as the first choice revascularisation procedure is feasible, safe and effective for limb salvage in a high percentage of diabetic patients. Clinical restenosis was an infrequent event and PTA could successfully be repeated in most cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
229
1
18

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 353 publications
(263 citation statements)
references
References 23 publications
13
229
1
18
Order By: Relevance
“…Studies on the treatment of PAD in diabetic foot disease are also scarce, and many questions remain to be answered. It is unclear at what degree of peripheral ischaemia intervention is cost-effective and which procedure-bypass or endovascular intervention-should be performed [29,30]. Treatment of infection in patients with PAD is another topic that has gained little attention.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the treatment of PAD in diabetic foot disease are also scarce, and many questions remain to be answered. It is unclear at what degree of peripheral ischaemia intervention is cost-effective and which procedure-bypass or endovascular intervention-should be performed [29,30]. Treatment of infection in patients with PAD is another topic that has gained little attention.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that PAD is commonly seen in patients on HD (6). In this day and age, PTA has become a common therapeutic standard for PAD in non-HD patients (7,8), and PTA is reported to be effective in patients on HD (9). However, vascular calcification and diffuse lesions may make the PTA procedure difficult to perform (10).…”
mentioning
confidence: 99%
“…The main studies in the literature [13,16,[23][24][25][26][27][28][29][30] reported, for endovascular treatment, a technical success rate of about 90 %, a negligible mortality rate, and a limb salvage rate at 3-5 years of 72-98 %.…”
Section: Discussionmentioning
confidence: 99%
“…The primary goal of PTA treatment is to restore the patency of at least one below-the-knee (BTK) vessel, preferably the tributary of the anatomical region of the ulcer [9]. Several studies have demonstrated good results in terms of patency and limb salvage after endovascular treatment of diabetic foot [10][11][12][13][14]. Many, however, are limited by the presence of a heterogeneous population with different stages of ischemia (claudication, rest pain, trophic lesions) and different treatment modalities, with PTA performed both in the above-the-knee (ATK) and BTK areas [15][16][17].…”
Section: Introductionmentioning
confidence: 99%